PELAYANAN KOMUNIKASI PERBANKAN DAN KEPUASAN NASABAH (PERSPEKTIF KOMUNIKASI ISLAM) - Perdana, Dian Adi (Islamic Communication Journal, 2019)
This article explains about the optimization of banking communication services that causes customer (campus community) dissatisfaction. Banking communication services as the main source of the problem are not being able to use internet banking in banking services, the lack of employees at the nearest BTN operational office, payment schedules that are often delayed because of internet integrity connecting between the campus and the bank is broken and service dissatisfaction has not yet reached the remote area. This study is a qualitative research by doing interview, observation, and documentation in data collection. The interactive analysis model is done in a descriptive qualitative manner and the data is presented with a SWOT analysis to determine the company's situation and strategy. The conclusion is the component of customer satisfaction in the form of: responsiveness, compliance, empathy, tangible, reliability and assurance which are elements of patterns of improvement in communication services have a positive influence on customer satisfaction in using banking services. This must be started and addressed by prioritizing customer needs. Researchers found that service influences customer satisfaction, which means that the greater the influence of service, the greater the satisfaction achieved by these customers, and these efforts continue to be carried out by BTN in maintaining customer trust in the company. Another thing is the need to optimize the strength they have to respond to opportunities that arise from external companies.Â